Analisis Faktor-Faktor Kinerja Sistem Keselamatan Kerja Konstruksi Proyek Bangunan Gedung Dinas Pendidikan Kota Sungai Penuh - Safwan, Safwan; Carlo, Nasfryzal; Putra, Wahyudi Utama (Jurnal Talenta Sipil, 2024)
The Indonesian government through the minister of Public Works and Public Housing has recently issued regulation Number 10 of 2021 concerning guidelines for construction safety management systems. The SMK3 Occupational Health and Safety Management System is part of the company's overall management system in order to control risks related to work activities in order to create a safe, efficient and productive workplace. The Construction Safety Management System is required to be implemented during construction because it is also part of the planning and control of the BPSDM PUPR project, 2021. In fact, in Sungai Full city in 2019-2021 experienced labor accidents, one of the projects was a school construction project at the Sungai Full City Education Office which could not be separated from the risk factors for accidents to its workers. Based on secondary data related to work accident information at the Sungai Full City education office School Building Construction Project, information was obtained that there had been 68 accident cases during 2019 – 2021. The purpose of this study is to identify the dominant factors and factors in the Implementation of Improving Performance Aspects of the Work Safety Management System of the Education Building Project in Sungai Full City, as well as providing solutions to improve the Performance of the Work Safety Management System. This study used quantitative methods by distributing questionnaires to respondents. The results of the research conducted there are 6 factors in the Work Safety Management System (SMKK) implemented in the implementation of the Education Building Project in Sungai Full City, consisting of Commitment factors, Project Managerial factors, K3 Regulations and Procedures factors, Worker Communication factors, Worker Competence factors, Work Environment factors, and Worker Involvement factors in K3.